Drosophila TRF2 and TAF9 regulate lipid droplet size and phospholipid fatty acid composition - Fan, Wei; Lam, Sin Man; Xin, Jingxue; Yang, Xiao; Liu, Zhonghua; Liu, Yuan; Wang, Yong; Shui, Guanghou; Huang, Xun (PLoS genetics, 2017)
The general transcription factor TBP (TATA-box binding protein) and its associated factors (TAFs) together form the TFIID complex, which directs transcription initiation. Through RNAi and mutant analysis, we identified a specific TBP family protein, TRF2, and a set of TAFs that regulate lipid droplet (LD) size in the Drosophila larval fat body. Among the three Drosophila TBP genes, trf2, tbp and trf1, only loss of function of trf2 results in increased LD size. Moreover, TRF2 and TAF9 regulate fatty acid composition of several classes of phospholipids. Through RNA profiling, we found that TRF2 and TAF9 affects the transcription of a common set of genes, including peroxisomal fatty acid β-oxidation-related genes that affect phospholipid fatty acid composition. We also found that knockdown of several TRF2 and TAF9 target genes results in large LDs, a phenotype which is similar to that of trf2 mutants. Together, these findings provide new insights into the specific role of the general transcription machinery in lipid homeostasis.